Using content and comparative analysis to contextualize the criteria for urban resiliency planning from international and US cities perspectives - Applegate, Joshua D.; Tilt, Jenna H. (Frontiers in Environmental Science, 2023)
This study focuses on how the term “urban resiliency” and other related terms are operationalized across spatial scales. The European Union and United Nations established international goals, targets, and the specific measurable indicators with both the European Green Deal and their 2030 Sustainable Development Goals (SDGs) to address climate change, with overarching goals of becoming the world’s first carbon neutral continent. Much of this work to “green” cities falls under the concepts of urban resiliency, Green Infrastructure (GI), and ecosystem services (ES). This study seeks to understand the criteria considered for planning, development, implementation and maintenance urban resiliency at city and international levels. By contextualizing and clarifying broad terms like resiliency, ecosystem services, and Green Infrastructure for planners, politicians, and people within communities, our comparative analysis provides detailed understanding of the similarities and differences between plans from a national perspective, along with analysis of city-to-city comparisons. Our results suggest there are differences in focus regarding key aspects of resiliency, as well as the strategies suggested for resilient cities. Key differences were found in the importance placed on transportation, the future role of Green Infrastructure, and definitions of ecosystem services. These differences may have potential impacts on outcomes for resiliency project development and maintenance.